Analysis of the Twelfth-Grade Arabic Textbook Based on Rusydi Ahmad Thuaimah’s Perspective - Kurniawan, Ilham; Muhaiban, Muhaiban (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study evaluates the quality of the Grade XII Arabic Language Textbook published by the Ministry of Religious Affairs of the Republic of Indonesia (2020) using the evaluative framework of Rusydi Ahmad Thuaimah. The research aims to determine the extent to which the textbook aligns with pedagogical and linguistic principles that integrate instructional and educational values. Employing a qualitative content analysis approach, data were collected through documentation and structured interviews with Arabic teachers. The analysis focused on four dimensions content, material organization, presentation, and book compilation. The results reveal that while the textbook adequately covers the four language skills, it remains unbalanced, with an emphasis on reading over writing activities. The material organization follows a spiral pattern, yet transitions between chapters lack cohesion. The presentation employs a communicative and contextual approach supported by visuals, although inconsistencies in image-text alignment and bilingual instructions persist. Technically, the book’s layout is well-structured, but it lacks clarity in defining its pedagogical orientation. Overall, the study concludes that the textbook partially fulfills Thuaimah’s criteria but requires revision to ensure better skill integration, thematic continuity, and multimodal coherence. The findings contribute to improving Arabic textbook development and offer theoretical insights into adapting Thuaimah’s evaluative model for the Indonesian educational context.